Analisis Penerimaan Petani Pengguna Aplikasi SiKePangMas (Aksi Ketahanan Pangan Masyarakat) berbasis Smart Farming di Kabupaten Sumba Timur - Mbana, Febyningsi Rambu Ladu; Saragih, Elsa Christin; Utu, Naomi Rambu; Malahina, Agung Kapading (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Smart farming is a solution to overcome food security problems in accordance with SDG's goal 2. In East Sumba Regency, it is realized by developing the Community Food Security Action (SiKePangMas) application, an Android-based application designed to help farmers determine the right commodities, planting calendars and forecasts of potential disaster hazards for more productive agriculture. The purpose of this study was to determine the level of acceptance and factors that influence the acceptance of farmer users of the SiKePangMas application. This study is a quantitative study, conducted from June to October 2025 in East Sumba Regency. ), The research respondents were 210 farmers who used the SIKePangMas application, determined by purposive sampling technique. The problem is solved using the Technology Acceptance Model (TAM) approach and the research model testing is carried out using the SEM-PLS approach with the help of the SmartPLS 4.0 application. The results of this study indicate that perceived usefulness (PU) has a positive and significant effect on attitudes towards use (ATU), perceived usefulness (PU) is proven to have a positive and significant effect on behavioral intentions of use (BIU), perceived ease of use (PEU) has a positive and significant effect on perceived usefulness (PU), perceived ease of use (PEU) is proven to have a positive and significant effect on attitudes towards use (ATU), attitudes towards use (ATU) are proven to have a positive and significant effect on behavioral intentions of use (BIU), behavioral intentions of use (BIU) have a very strong and significant positive effect on actual use (AU) of the SiKePangMas application. Attitudes and intentions are proven to be the main predictors that determine the level of use of the SiKepanMas application in farmer farming in East Sumba Regency.